Perbedaan pemberian cairan isotonis dan hipotonis terhadap osmolalitas plasma pada penderita gangguan intrakranial akut di RSUP Sanglah, Denpasar, Bali - Wayan Sulaksmana Sandhi Parwata; I Nyoman Budi Hartawan; I Gusti Ngurah Suwarba; Ida Bagus Suparyatha; Dyah Kanya Wati (Intisari Sains Medis, 2019)
Background: Acute intracranial disturbance can lead to increased occurrence of cardiovascular activity that will lead to a decrease of sodium reabsorption in the kidney. The proper selection of liquid on acute intracranial disorders can help reduce damage to brain tissue. This study aims to determine differences in plasma osmolality levels in patients with acute intracranial disorders who get isotonic or hypotonic fluid.Methods: A cross-sectional observational study was carried out among 60 patients aged 1 month-12 years who experienced acute intracranial disturbance in Sanglah General Hospital during 2017. The difference in plasma osmolality in each group was tested using Mann-Whitney due to the data were not normally distributed. There was a significant difference in osmolality levels in the group receiving isotonic fluid compared with hypotonic (p <0.001)Results: Males were predominant in the isotonic group (66.7%) and hypotonic (70%). Good nutritional status was found in both groups (90%; 83.33%). Encephalitis is the most common cause of acute intracranial disturbance, namely 14 (46.67%) cases of istononic groups and 12 (40%) cases of hypotonic groups. The median value (IQR) of plasma and sodium osmolality levels that obtained isotonic fluid showed a difference in values of 139(6) mEq/L and 287(20) mOsm/kg H2O in isotonic and 132 (7) mEq/ L and 273(16) mOsm/kg H2O in hypotonic. There was a significant difference in osmolality levels in the group receiving isotonic fluid compared to hypotonic (p<0.001)Conclusion: There are differences in levels of osmolality in patients with acute intracranial disorders who get isotonic fluid compared to groups that get hypotonic fluid.